A controlled study of sleep related disordered breathing in obese children. Issue 12 (11th December 2003) - Wing, Y K; Hui, S H; Pak, W M; Ho, C K; Cheung, A; Li, A M; Fok, T F
Abstract : Background: Unlike the adult sleep related disordered breathing (SDB) patients who are typically obese, the relation between obesity and childhood SDB is not clear. Aims: To investigate whether obese children are more at risk of obstructive SDB when compared to normal population, and whether this risk is potentiated by the presence of pharyngeal lymphoid tissue. Methods: Forty six obese children (age 10.8 (SD 2.3) years; BMI 27.4 (SD 5.1)), and 44 sex and age matched normal weight children (age 11.7 (SD 2.1) years; BMI 18 (SD 1.8)) were studied. All children underwent a set of physical examinations (including the upper airways) and sleep studies. Results: The obese children were different from the normal weight children in terms of type (predominantly obstructive), frequency, and severity of respiratory disturbances. Depending on the criteria used, 26% or 32.6% of obese children had SDB; 2.3% of normal controls had OAI ⩾1 and 4.5% had RDI ⩾5. Presence of SDB was related to presence of tonsils (size >2; range 0–4) (OR 12.67, 95% CI 2.14 to 75.17) and BMI (OR 1.20, 95% CI 1.08 to 1.33). Conclusions: Results suggest that obese children are at increased risk of obstructive SDB; the presence of any pharyngeal lymphoid tissue enlargement in obese children should therefore be aggressively managed.